(3SQM GdYjhf aj TQM QSGdI GHf RjOhfs - (3eMeO Hf eMeO Hf eMeO Hf GdMSf GdLPGej GdaGQbj GdeUQj, GHf fHGJg , LeGd GdOjf CHh HcQ,J (B768 (3g` s; (3GHf RjOhf , CHh GdhdjO CMeO Hf YHO Gddg Hf ZGdH Hf RjOhf GdeNRhej GdCfOdSj, CHh GdhdjO,J (B463 (3g` s ((3YeQ CfSi Hf eMeO OjH GdTgjQ HGHf GdUbYGf GdHjQhJi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjLH GdMeO EdG dg hHYO aEfi CeQJ HTQM QSGdI GdhRjQ CHh GdhdjO GHf RjOhf s
(3BNQgG (B:s
(3JeJ GdQSGdI hTQMgG hGdOdGdI hdeMgG hdG COYi ajgG ZjQ EfJNGH GdCNHGQ hGNJjGQ GdeJecf ef GdfXGe hGdfKGQ hYdi GdLedI aai YhGWa ef YQVJ Ydjg GdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs